Ce=O Terminated CeO2. Issue 25 (11th May 2021) - Grinter, David C.; Allan, Michael; Yang, Hyun Jin; Salcedo, Agustín; Murgida, Gustavo E.; Shaw, Bobbie‐Jean; Pang, Chi L.; Idriss, Hicham; Ganduglia‐Pirovano, M. Verónica; Thornton, Geoff
Abstract: Multiply bonded lanthanide oxo groups are rare in coordination compounds and have not previously been reported for a surface termination of a lanthanide oxide. Here we report the observation of a Ce=O terminated ceria surface in a CeO2 (111)‐( 3 × 3 )R30° reconstruction of ≈3 nm thick ceria islands prepared on Pt(111). This is evidenced by scanning tunnelling microscopy (STM), low energy electron diffraction (LEED) and high‐resolution electron energy loss spectroscopy (HREELS) measurements in conjunction with density functional theory (DFT) calculations. A Ce=O stretching frequency of 775 cm −1 is observed in HREELS, compared with 766 cm −1 calculated by DFT. The calculations also predict that the Ce=O bond is weak, with an oxygen vacancy formation energy of 0.85 eV. This could play an important role in the facile removal of lattice oxygen from CeO2, accompanied by the reduction of Ce IV to Ce III, which is a key attribute of ceria‐based systems in connection with their unique catalytic properties. Abstract : A combined experimental and computational study of the ( 3 × 3 )R30° reconstruction of the CeO2 (111) surface of an ultrathin ceria film is presented. The evidence collected indicates that the film is terminated by Ce=O groups.